Komunikasi Organisasi SPBUN PTPN IV Sosa Dalam Meningkatkan Kinerja Karyawan - Atah Sulhansyah; Fadhil Pahlevi Hidayat (Universitas Muhammadiyah Sumatera Utara, 2023)
Organizational communication is the process of creating and exchanging messages in a network of interdependent relationships to cope with uncertain or ever-changing environments. The purpose of this study is to find out